Sosialisasi Pembiayaan dalam Perspektif Ekonomi Syariah - agusta, silvia (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2023)
Islamic economics is one of the economic systems that has the fastest development in the world. Many countries in Europe and America have implemented the Islamic economic system, because the concept of Islamic economics places more emphasis on welfare and justice for the parties involved. However, in Indonesia itself, the sharia economic system is still foreign to Indonesian society, especially to rural communities. but Indonesian people tend to choose conventional banks. Because they think that the Islamic economic system has complicated procedures. From the lack of public knowledge about the Islamic economic system, especially in the practice of granting credit, it has triggered many creditors to provide credit by implementing an interest system with high interest rates. Of course, the practice of giving credit like that is very detrimental and burdensome to the people who are the creditors. This is what prompted the author to make socialization of Islamic economic perspective financing. This is intended so that people can understand the sharia economic system directly so that in the future they can differentiate between sharia-based and conventional financing systems Keywords: Financing, Economy, Sharia